2011
DOI: 10.1586/erd.11.28
|View full text |Cite
|
Sign up to set email alerts
|

Renaissance of contact x-ray therapy for treating rectal cancer

Abstract: Contact x-ray therapy (CXRT) with 50 kV has proven to be an efficient radiation therapy technique to achieve local control and rectal preservation for early rectal adenocarcinoma. Despite these results, CXRT has not been used due to the shortage of the no longer manufactured Philips RT 50™ unit. Recently, a new CXRT machine (Papillon 50™) became available on the market. This machine delivers a beam of 50 kV with a dose rate close to 15 Gy/min and has a percentage depth dose of 50% at 6-7 mm. The applicator siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 28 publications
0
25
0
5
Order By: Relevance
“…La calibration de chambres d'ionisation dédiées au 50 kV et aux petits champs (1 à 2 cm de diamètre) est du ressort des laboratoires nationaux de métrologie et peut encore progresser pour une plus grande exactitude. Le développement de logiciels de planimétrie pour le 50 kV apparait prometteur sous un angle pédagogique mais aussi dans la perspective de sommation de dose entre plan de traitement 50 kV et irradiation à haute énergie ou par curiethérapie voire radiothérapie per opératoire [9]. Les perspectives de développement de cette technique de CXRT et des appareils Papillon sont multiples et prometteuses.…”
Section: Discussionunclassified
“…La calibration de chambres d'ionisation dédiées au 50 kV et aux petits champs (1 à 2 cm de diamètre) est du ressort des laboratoires nationaux de métrologie et peut encore progresser pour une plus grande exactitude. Le développement de logiciels de planimétrie pour le 50 kV apparait prometteur sous un angle pédagogique mais aussi dans la perspective de sommation de dose entre plan de traitement 50 kV et irradiation à haute énergie ou par curiethérapie voire radiothérapie per opératoire [9]. Les perspectives de développement de cette technique de CXRT et des appareils Papillon sont multiples et prometteuses.…”
Section: Discussionunclassified
“…Further clinical trials are recommended, however, and proper training and expertise are essential. Rectal cancer treatment with the Papillon unit is being investigated by the CONTEM observational studies, 17 and the proposed OPERA Phase III randomized trial.…”
Section: 53mentioning
confidence: 99%
“…It has been shown that a dose of 92 Gy (2 Gy/fraction equivalent) is necessary to control only 50 % of T3 tumors [32•], and on the other hand, the maximum tolerable dose of the rectum is close to 75 Gy [33][34][35][36]. When considering these two opposite parameters, it is highly probable that mainly endocavitary well-targeted irradiations techniques (radioactive or X-ray brachytherapy and not teletherapy with external beam) will be able to achieve these balanced objectives [37][38][39][40][41]. It must also be kept in mind that by far the most powerful predictive factor of radiation tumor response is the tumor volume [42].…”
Section: Neoadjuvant Treatments and Strategies To Improve Present Resmentioning
confidence: 99%